Bone and Cartilage Interfaces With Orthopedic Implants: A Literature Review - Grzeskowiak, Remigiusz M.; Schumacher, Jim; Dhar, Madhu S.; Harper, David P.; Mulon, Pierre-Yves; Anderson, David E. (Frontiers in Surgery, 2020)
The interface between a surgical implant and tissue consists of a complex and dynamic environment characterized by mechanical and biological interactions between the implant and surrounding tissue. The implantation process leads to injury which needs to heal over time and the rapidity of this process as well as the property of restored tissue impact directly the strength of the interface. Bleeding is the first and most relevant step of the healing process because blood provides growth factors and cellular material necessary for tissue repair. Integration of the implants placed in poorly vascularized tissue such as articular cartilage is, therefore, more challenging than compared with the implants placed in well-vascularized tissues such as bone. Bleeding is followed by the establishment of a provisional matrix that is gradually transformed into the native tissue. The ultimate goal of implantation is to obtain a complete integration between the implant and tissue resulting in long-term stability. The stability of the implant has been defined as primary (mechanical) and secondary (biological integration) stability. Successful integration of an implant within the tissue depends on both stabilities and is vital for short- and long-term surgical outcomes. Advances in research aim to improve implant integration resulting in enhanced implant and tissue interface. Numerous methods have been employed to improve the process modifying both stability types. This review provides a comprehensive discussion of current knowledge regarding implant-tissue interfaces within bone and cartilage as well as novel approaches to strengthen the implant-tissue interface. Furthermore, it gives an insight into the current state-of-art biomechanical testing of the stability of the implants. Current knowledge reveals that the design of the implants closely mimicking the native structure is more likely to become well integrated. The literature provides however several other techniques such as coating with a bioactive compound that will stimulate the integration and successful outcome for the patient.